1991
DOI: 10.1017/s0252921100066379
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Detection in the Near Earth Space Environment Aboard the Long Duration Exposure Facility Ldef: Cosmic or Terrestrial?

Abstract: Examination of surfaces exposed for more than five and a half years, from detectors with unique attitude stabilisation relative to the orbital velocity vector, offers scope for examining definitively the sources of hypervelocity space particulates. Surfaces reveal discrete crater morphologies, crater size distributions and incident flux distributions. Discrete crater studies will later also reveal the chemistry of residues which can, especially via the capture cell principle, lead to elemental analysis of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The data indicate the presence of particles with a diameter of a few tenths of microns (mass of 10"" gm) in earth bound orbits. Data from IDE experiment on LDEF are consistent with these results (Singer et al,1990), as well as measurements reported by Singer (Singer and Stanley,1980 The size distribution shows a good agreement with comparable near-earth data obtained by McDonnell (McDonnell et al 1991); flux on the west face of LDEF is about 20 times lower than on the east face, for large particles. Most of the particles impacting this face should be interplanetary dust particles, not orbital debris.…”
Section: Preliminary Resultssupporting
confidence: 89%
“…The data indicate the presence of particles with a diameter of a few tenths of microns (mass of 10"" gm) in earth bound orbits. Data from IDE experiment on LDEF are consistent with these results (Singer et al,1990), as well as measurements reported by Singer (Singer and Stanley,1980 The size distribution shows a good agreement with comparable near-earth data obtained by McDonnell (McDonnell et al 1991); flux on the west face of LDEF is about 20 times lower than on the east face, for large particles. Most of the particles impacting this face should be interplanetary dust particles, not orbital debris.…”
Section: Preliminary Resultssupporting
confidence: 89%